2022
DOI: 10.1186/s13023-022-02309-6
|View full text |Cite
|
Sign up to set email alerts
|

Designing rare disease care pathways in the Republic of Ireland: a co-operative model

Abstract: Background Rare diseases (RDs) are often complex, serious, chronic and multi-systemic conditions, associated with physical, sensory and intellectual disability. Patients require follow-up management from multiple medical specialists and health and social care professionals involving a high level of integrated care, service coordination and specified care pathways. Methods and objectives This pilot study aimed to explore the best approach for develo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 35 publications
2
14
0
2
Order By: Relevance
“…An adult 22q clinic may also help to further reduce fragmented medical care experienced by the adults with 22q11DS, where participants describe a decline in the quality of care. This is supported by recent findings by Ward et al (2022) reporting significant gaps in healthcare services for adults with 22q11DS due to a lack of transition care pathways. The findings also emphasized a need for children with 22q11DS to be encouraged to develop a good relationship with their GP as they enter their teen years, to help with the transition to adult care and be empowered as young adults.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…An adult 22q clinic may also help to further reduce fragmented medical care experienced by the adults with 22q11DS, where participants describe a decline in the quality of care. This is supported by recent findings by Ward et al (2022) reporting significant gaps in healthcare services for adults with 22q11DS due to a lack of transition care pathways. The findings also emphasized a need for children with 22q11DS to be encouraged to develop a good relationship with their GP as they enter their teen years, to help with the transition to adult care and be empowered as young adults.…”
Section: Discussionsupporting
confidence: 83%
“…Participants in the current study reported becoming the experts about their child's condition due to non‐genetics HCPs having little understanding of 22q11DS, which is well‐documented in wider rare disease research (Budych et al, 2012; Ward et al, 2022). The findings suggest an association between HCPs' low awareness of 22q11DS with participants' perceived lack of empathy from HCPs.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations